Suppression of plasticization in polysulfone membranes for gas separations by heat-treatment technique - Ismail, A. F.; Lorna, W. (Elsevier, 2003)
polysulfone (Udel P1700). Two types of membranes with heat treated and untreated were prepared to study the effect of heat-treatment process on its permeation properties. For untreated membrane, CH4 permeation rate remained almost constant with applied gas pressure. CO2 permeation rate exhibited an increase with increasing feed pressure, indicating that CO2 plasticized the membrane material. The asymmetric membranes were given different heating temperature and different treatment durations to investigate the suppression of undesirable CO2 plasticization. Permeation rates were reduced with the intensity of heat treatment. Experimental results showed that the membranes were stabilized against CO2 plasticization after heat-treatment process, especially at temperature of 140 Â°C. Heating temperature has tremendous effect on the gas transport properties for treated membrane at 180 Â°C, giving an unusual behavior of CO2. Plasticization is a pressure-dependent and time-dependent phenomenon. For the original membrane, the relaxation permeation rate of CO2 is linearly related to the logarithmic experimentation time. The CO2 permeation rate for treated membrane maintains at steady state over the applied feed pressures. Thus, the heat-treatment method to suppress CO2 plasticization and achieve better asymmetric membrane performance was effective.